A Zwitterionic Heterobimetallic Gold–Iron Complex Supported by Bis(N-Heterocyclic Imine)Silyliumylidene - Hanusch, Franziska; Munz, Dominik; Sutter, Jörg; Meyer, Karsten; Inoue, Shigeyoshi (Angewandte Chemie International Edition, 2021)
The facile synthesis of the first bis-N-heterocyclic imine-stabilized chlorosilyliumylidene 1 is reported. Remarkably, consecutive reaction of 1 with PPh3AuCl and K2Fe(CO)4 gives rise to the unique heterobimetallic complex 1,2-(MesNHI)2-C2H4-ClSiAuFe(CO)4 (4). The overall neutral complex 4 bears an unusual linear Si−Au−Fe structure and a rare anagostic interaction between the d10-configured gold atom and a CH bond of the mesityl ligand. According to the computational analysis and 57Fe Mössbauer spectroscopy, the formal Fe-oxidation state remains at −II. Thus, the electronic structure of 4 is best described as an overall neutral—yet zwitterionic—heterobimetallic “Si(II)+-Au(I)+-Fe(-II)2−”-silyliumylidene complex, derived from double anion exchange. The computational analysis indicates strong hyperconjugative back donation from the gold(I) atom to the silyliumylidene ligand.
CRIS-Team Scopus Importer:2021-10-01
Keywords: anagostic interactions; gold; iron; silicon; zwitterionic complexes